Diseases Of Old People Referring To Elderly Centers Of Tehran - Ali Darvishpoor Kakhki; Jilla Abed Saeedi; Ali Delavar (Tehran University of Medical Sciences, 2014)
Background and Aim: Aging is a natural experience which is usually accompanied by a variety of diseases. Hence, this research was conducted to study the elderly people's disease rate and the number of times they refer to medical centers in Tehran. Materials and Methods: This descriptive analytical study was conducted on the old people referring to the Elderly Centers in Tehran in 2012. For data collection purposes, valid and reliable self-report demographic and disease questionnaires were used. The data were analyzed by SPSS software together with T-test and one-way ANOVA.  Results: Four hundred old people participated in this study. Of the participants, 300 (75%) were female and 100 (25%) male with a mean age of 67.65 (±6.38) years. Besides, 160 (40%) people had heart diseases, 137 (34.3%) muscoskeletal diseases, and 83 (20.8%) endocrine diseases. Moreover, 381 (95.2%) participants had referred to doctors and therapeutic centers at least once during the last year. Furthermore, 177 subjects (44.2%) were hospitalized at least once last year. Conclusion: The prevalence of diseases in elderly people is more than expected. Most old people refer to doctors and therapeutic centers, which is indicative of the fact that they suffer from diseases and need varied health services.